The Effect of Coffee Brand Identity on Food Security in Sindang Marga Village, Ogan Lima District: Pengaruh Identitas Merek Kopi terhadap Ketahanan Pangan di Desa Sindang Marga, Kabupaten Ogan Lima - Eko Abadi Novrimansyah; Rosy Febriani Daud (Institute of Educational, Research, and Community Service, 2023)
Today, amidst the development of digital technology and the creative industry sector in Indonesia, many companies are optimising the use of creative copywriting in building their brand identity. Among the seventeen subsectors of Indonesia's creative industry, the food and beverage industry is one of the most developed. Copywriting is closely related to brand promotion activities because the message conveyed through copywriting is a bridge from the brand to consumers so that the products sold have a different character from competitors. Therefore, this research examines the influence of creative copywriting on the brand identity of coffee shops in Bandar Lampung by taking five case studies and classifying them based on the copywriting used. The results obtained from this research can later be used as a reference for consideration of advertising text when designing corporate identity